Pengaruh Faktor Ketergunaan (Usability) Sistem ERP Oracle Cloud terhadap Efektivitas Implementasinya pada PT Bumi Sarana Utama di Indonesia - Fadhilah Maulidya Ikhsan; Muhammad Asdar; Jusni Jusni (Hasanuddin Journal of Business Strategy, 2019)
ERP systems (Enterprise Resource Planning) provide companies with software that combines functional pieces with a focus on the processes.This study aims to determine the effect of usability of the Oracle Cloud ERP System on the effectiveness of its implementation at PT. Bumi Sarana Utama in Indonesia. The design of this study is to use a quantitative approach. In this study there are two variables, namely the dependent variable and the independent variable. The population in this study are food and beverage industry companies. The sampling method used is random sampling. Data collection was carried out using library research and field research. Data analysis was performed using multiple linear regression analysis using the SPSS 23.0 system. The results of this study indicate that (1) There is a positive and significant effect on learnability variables on the implementation of the Oracle Cloud ERP system at PT. Bumi Sarana Utama. (2) There is a positive and insignificant effect on the efficiency variable on the implementation of the Oracle Cloud ERP system at PT. Bumi Sarana Utama. (3) There is a positive and insignificant effect on the memorability variable on the implementation of the Oracle Cloud ERP system at PT. Bumi Sarana Utama. (4) There is a positive and insignificant effect on the error variable on the implementation of the Oracle Cloud ERP system at PT. Bumi Sarana Utama. (5) There is a positive and not significant effect on the satisfaction variable on the implementation of the Oracle Cloud ERP system at PT. Bumi Sarana Utama